Responsibilities in the Service Performance of the Manpower Service of Sidoarjo Regency (Administrative Responsibility Perspective) - Ayun, Siti Qurrotu (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2019)
Public services in Indonesia, seen from the service accountability, are still not optimal. Meanwhile, there are problems regarding the performance of service employees to the community, the lack of service delivery and lack of socialization and training on the performance of service employees at the Sidoarjo Regency Manpower Office. The purpose of this study is to identify and describe the service performance of the Sidoarjo Regency Manpower Office in the perspective of administrative responsibility. The location of this research was carried out at the Sidoarjo Regency Manpower Office. This research method uses descriptive qualitative by using purposive sampling technique in determining informants. Qualitative data aggregate techniques were obtained through interviews, observation and documentation. Technique of analyzing data by reducing data, presenting data and drawing conclusions. The results showed that the service performance of the Sidoarjo Regency Manpower Office in providing services to the community needs to be increased in socialization so that employees can improve service performance properly or maximally. Administrative responsibility in service performance shows that the responsibility carried out by employees to the community is very good in providing these services